REPRESENTASI PSIKOLOGI PEREMPUAN AKIBAT BUDAYA PATRIARKI DALAM CERPEN “PEREMPUAN ITU PERNAH CANTIK” KARYA MASHDAR ZAIDAL - Pasaribu, Christin; Firmansyah, Dodi (LPPM Institut Pendidikan Nusantara Global, 2023)
Literary works are fictional writings that describe the reality of people's lives. In writing a work, the author expresses his thoughts based on experiences in society. The literary work in the form of a short story entitled